Oxidative stress in pancreatic alpha and beta cells as a selection criterion for biocompatible biomaterials. (January 2021) - Sthijns, Mireille M.J.P.E.; Jetten, Marlon J.; Mohammed, Sami G.; Claessen, Sandra M.H.; de Vries, Rick H.W.; Stell, Adam; de Bont, Denise F.A.; Engelse, Marten A.; Mumcuoglu, Didem; van Blitterswijk, Clemens A.; Dankers, Patricia Y.W.; de Koning, Eelco J.P.; et al.
Abstract: The clinical success rate of islet transplantation, namely independence from insulin injections, is limited by factors that lead to graft failure, including inflammation, acute ischemia, acute phase response, and insufficient vascularization. The ischemia and insufficient vascularization both lead to high levels of oxidative stress, which are further aggravated by islet encapsulation, inflammation, and undesirable cell-biomaterial interactions. To identify biomaterials that would not further increase damaging oxidative stress levels and that are also suitable for manufacturing a beta cell encapsulation device, we studied five clinically approved polymers for their effect on oxidative stress and islet (alpha and beta cell) function. We found that 300 poly(ethylene oxide terephthalate) 55/poly(butylene terephthalate) 45 (PEOT/PBT300) was more resistant to breakage and more elastic than other biomaterials, which is important for its immunoprotective function. In addition, it did not induce oxidative stress or reduce viability in the MIN6 beta cell line, and even promoted protective endogenous antioxidant expression over 7 days. Importantly, PEOT/PBT300 is one of the biomaterials we studied that did not interfere with insulin secretion in human islets. Highlights: PEOT/PBT300 does not induce oxidative stress in pancreatic alpha and beta cells. PET and PVDF induce oxidative stress in alpha cells, but not in beta cells. Beta cells can protect themselves against oxidative stress induced by certain biomaterials.